Pathways to decarbonising the transport sector: The impacts of electrifying taxi fleets - Caulfield, Brian; Stefaniec, Agnieszka (My University, 2023)
The impacts of climate change have prompted governments to pledge to introduce policies aiming to limit the increasing temperature. One of the strategies involves reducing and, eventually, eliminating internal combustion engines in favour of electric vehicles. This strategy has been implemented by many transportation services, and FREE NOW has pledged to be carbon neutral by 2030. This study analyses the FREE NOW taxi fleet composition in Dublin in 2021 and investigates the reduction in emissions from fully electrifying the fleet. The analysis uses an emissions tool to model a combination of scenarios, consisting of different vehicle powertrain and fuel type configurations. An emission factor is applied to the EVs to calculate the emissions produced by the electricity used to power the vehicles. The results show a 77% decrease in carbon dioxide emissions from fully electrifying the fleet. Multi-criteria analysis is used to assess the strengths and weaknesses of each scenario developed. The S-5 scenario, consisting of the EVs only, scored the highest for many of the criteria. S-5 was identified as the best option for the taxi fleet, followed closely by S-4 involving an upgrade to all plug-in hybrid EVs. The S-4 scenario seems to be a good alternative when an EV is too expensive or access to charging infrastructure is not provided. The infrastructure currently available in Dublin will not accommodate the all-EV taxis target by 2030.
PUBLISHED
Keywords: Taxi; Electric vehicle; Emission modeling; Multi-criteria analysis; Scenario analysis; Net-zero target; Smart & Sustainable Planet; Environmental aspects of transportation; Transport